Keanekaragaman kupu-kupu (Lepidoptera: Papilionoidea) di Kawasan Pusat Pendidikan Konservasi Alam Bodogol, Taman Nasional Gunung Gede Pangrango, Jawa Barat: Diversity of butterflies (Lepidoptera: Papilionoidae) in the Bodogol Nature Conservation Education Center Area, Gunung Gede Pangrango National Park, West Java - Ruslan, Hasni; Satiyo, Abda'u; Yenisbar, Yenisbar (Perhimpunan Entomologi Indonesia, 2023)
Butterflies are a group of insects with high species diversity and are closely related to environmental factors that affect their presence and abundance in a habitat. This study aimed to analyze the diversity and abundance of butterfly populations in PPKA Bodogol, Sukabumi, West Java. Observation of butterflies was carried out using a 700 m long transect method using a camera and sweeping nets along the existing paths in two locations, namely heterogeneous forest and homogeneous forest. Butterfly observations were carried out from 08.00–12.00 in the morning. Based on the research results, 78 species (261 individuals) were found in heterogeneous forests, and 39 species (158 individuals) in homogeneous forests, which belong to 5 families, namely Lycaenidae, Nymphalidae, Papilionidae, Pieridae, and Rionidae. The Nymphalidae is a family that has the highest number of species and individuals compared to other families. The butterfly diversity index in heterogeneous forests was the highest, whereas in homogeneous forests was moderate. The similarity value of butterfly composition is <50%, which means that the composition of butterflies found in the two habitats is not the same. The diversity index of butterflies in heterogeneous forests was higher than in homogeneous forests. There was no significant difference from the Hutchinson test. Species evenness index values in the two habitats showed almost the same value, 0.9 in heterogeneous forests and 0.8 in homogeneous forest. The existence, diversity, and abundance of butterflies in a habitat are closely related to the type of habitat and the abiotic and biotic elements present in it.